The Influence of Murabahah, Musyarakah, Ijarah and Qardh Financing on The Net Profit of Sharia Commercial Banks (BUS) in Indonesia 2017-2022 - Wirman; Amilin; Rini (Accounthink : Journal of Accounting and Finance, 2024)
The purpose of this study is to ascertain how partial and simultaneous financing for ijarah, murabahah, shariah, and qardh affects the net profit of Indonesia's sharia commercial banks between 2017 and 2022. All Islamic commercial banks registered with the Otoritas Jasa Keuangan (OJK) for the period of 2017–2022 comprise the population included in this study. The Purposive Sampling Method technique was employed to obtain the samples that were used. Verification, multiple linear regression analysis, and quantitative descriptive methods are the data analysis techniques employed. The findings demonstrated that net profit was significantly impacted by murabahah financing, significantly impacted by ijarah financing, nil by musharakah financing, and unaffected by qardh financing.